Illustrating Quality of Life (QOL) - Dewan, Ashraf M.; Nahar, K.; Kawamura, Yohei (Springer, 2013)
The objective of this chapter is to develop a quality of life (QOL) index atcommunity level in the Dhaka City Corporation (DCC) area, which could describethe spatial patterns of QOL. Using remote sensing, census and other spatial data, afactor analysis was carried out to develop the different dimensions of QOL. Threeprincipal factors were extracted from the analysis: environmental, economic anddemographic. These three factors were then combined in a Geographic InformationSystems (GIS) environment to construct a synthetic QOL for the study area. Theresults were subsequently validated using regression analysis, which revealed a betterprediction of QOL based on environmental and socioeconomic variables. Interestingly,only a small portion of the population (1.4 %) in the study area was shown tohave good QOL. As higher urban growth driven by rapid rural-urban migration isexpected in Dhaka in the coming years, this study will be of substantial help for urbanplanners and policymakers in formulating related policies to ensure a better livingenvironment for its inhabitants.